Detection of Plasmodium falciparum Histidine-rich Protein II in Saliva of Malaria Patients - Wilson, N.O.; Adjei, A.A.; Anderson, W.; Baidoo, S.; Stiles, J.K. (American Journal of Tropical Medicine and Hygiene, 2008)
Detection of Plasmodium falciparum parasites in patients with malaria necessitates drawing blood, which increases the risk of accidental infections and is poorly accepted in communities with blood taboos. Thus, non-invasive, cost-effective malaria tests that minimize the need for blood collection are needed. Plasmodium falciparum histidine-rich protein II (PfHRP II) levels in plasma and saliva were compared in malaria-positive and -negative patients in Ghana. Plasma and saliva obtained from 30 thick-film positive and 10 negative children were evaluated for PfHRP II by ELISA. Among the 30 children with positive blood smear, 16 (53%) were PfHRP II positive in plasma and 13 (43%) had PfHRP II positive saliva. The sensitivity of PfHRP II detection was 53% for plasma and 43% for saliva. The specificity was 100% with no false positive for both plasma and saliva when compared with blood smear. Thus, rapid detection of PfHRP II antigen in saliva may be a useful non-invasive and cost-effective malaria diagnostic technique.